TEXTUALITY STANDARDS IN ACADEMIC VERSUS NON-ACADEMIC DISCOURSES: https://doi.org/10.5281/zenodo.17283086 - Nazarov , Asilbek; Solnyshkina , Marina (International scientific and practical conference, 2025)
This paper examines the application of textuality standards in academic and non-academic discourses. Using Beaugrande and Dressler’s (1981) model of seven standards—cohesion, coherence, intentionality, acceptability, informativity, situationality, and intertextuality—the study compares how these criteria are realized in two different communicative domains. The analysis reveals that academic discourse prioritizes cohesion, coherence, and intertextuality to establish scientific credibility and precision, while non-academic discourse emphasizes intentionality, informativity, and situationality to ensure accessibility and engagement for broader audiences. The findings highlight the genre-specific manifestations of textuality and their implications for discourse studies, pedagogy, and translation practice.